Development of multifunctional polymer nanocomposites with carbon-based hybrid nanostructures synthesized from ferrocene. (February 2016) - Riquelme, Juan; Garzón, Cristhian; Bergmann, Carlos; Geshev, Julian; Quijada, Raúl
Graphical abstract: Highlights: Carbon-based 3D hybrid nanoparticles by means of CVD method were synthesized. Magnetic polymeric nanocomposites by melt mixing of polypropylene were developed. Carbon-based hybrid nanoparticles modified the diamagnetic nature of neat polymer. Magnetite in carbon-based filler does not affect the electrical performance. Magnetite in carbon-based filler increases the mechanical behavior of the matrix. Abstract: This paper proposes the development of isotactic polypropylene (iPP) nanocomposites with magnetic carbon-based hybrid fillers, which contain magnetite, by melt mixing at 190 °C. The carbon-based fillers such as carbon nanotubes (CNTs) were synthesized via chemical vapor deposition (CVD), using ferrocene as catalyst and precursor synthesis, and using silica (SiO2 ) or thermally reduced graphene oxide (TrGO) as support, obtaining SiO2 /CNTMagnetite and TrGO/CNTMagnetite hybrid nanostructures, respectively. Mechanical, electrical and magnetic behaviors of the iPP nanocomposites with magnetic CNTs were evaluated; their performance against iPP composites with commercial CNTs was compared. The results show that the electrical conductivity of the iPP nanocomposites is not affected by the presence of magnetite, reaching a percolation threshold similar to that obtained in iPP nanocomposites with commercial CNTs. Likewise, the presence of CNTs with magnetic particles changes the diamagnetic nature of the polymeric matrix, transforming it into a ferromagnetic composite at low filler concentrations (2 wt.%).